Hippocampal infusion of lipopolysaccharide induces immune responses and results in seizures in rats. Issue 4 (1st March 2017) - Zhang, Yanxiang; Sun, Xuwen; Nai, Yu; Ba, Maowen; Fu, Qiang; Wu, Fei
Abstract : Recent studies suggest that epileptic seizures might be facilitated by immune reactions in the brain. However, it remains unclear whether inflammatory reactions could result in acute and chronic epileptic seizures in vivo . In the present study, we investigated whether a hippocampal infusion of lipopolysaccharide (LPS) can induce epileptic seizures in rats. We also aimed to elucidate the molecular mechanisms that underpin this phenomenon. Male Wistar rats received a 1.5 μl infusion of either LPS (5 µg/μl), normal saline, or kainate (KA) (0.4 µg/μl) into the right dorsal hippocampus. No seizures were observed in the normal saline group and associated electroencephalograms showed basic rhythms. Various grades of seizures were observed in rats from the LPS and KA groups, and electroencephalograms were characterized by seizure activities (sharp waves or spikes). In the chronic phase (8 weeks after injection), astrocytes proliferated and the number of neurons decreased in the hippocampus of the rats in the LPS and KA groups. When assessed at the acute phase (within 6 h after injection), the expression of interleukin 1β, tumor necrosis factor α, and neuronal nitric oxide synthase was significantly increased in the hippocampus of the LPS groups. The results of the present study indicate that hippocampal infusion of LPS can activate innate immune responses of glial cells, thereby inducing epileptic seizures and hippocampal sclerosis in rats.